Effect of Substrate Temperature on the Critical Current Density in the YBa2Cu3O7-x Superconducting Films - Duc, Tran Hai; Nhan, Duong Thi Thanh; Sinh, Nguyen Huy (VNU Journal of Science: Mathematics - Physics; Vol 32 No 2, 2016)
Abstract: A comparative study of effect of substrate temperature (T s ) on the critical current density (J c ) in YBa 2 Cu 3 O 7-x (YBCO) superconducting films is reported. YBCO superconducting films were fabricated by using the pulsed laser deposition (PLD) technique. The substrate temperature was ranged from 720 to 800 o C in order to find its optimum value for depositing YBCO films. Results of structural measurements the YBCO films showed that the lattice parameter c were depended on the substrate temperature. The largest value of lattice parameter c calculated from Xray diffraction patterns was obtained for the YBCO film deposited at 780 o C. More interestingly, the critical current density of the YBCO films measured at 65 K also depended on the substrate temperature. The highest value of critical current density of ~ 5.7 MA/cm 2 was also found at the YBCO film deposited at 780 o C. Consequently, the optimum value of T s of 780 o C might be concluded. Keywords:   YBCO, thin film, J c .